Stress among sports coaches: a systematic review - Santos, Felipe Gustavo dos; Costa, Varley Teoldo da (Cuadernos de Psicología del Deporte, 2018)
The aim of the present study was to perform a systematic review of the literature on stress among sports coaches. Articles published from 1994 to 2016 were selected from seven electronic databases. The following keywords/terms, in English, Spanish and Portuguese, were used in the search: stress, estrés, estresse, coach(es),entrenador(es),treinador(es). The search for articles in all the databases was independently performed by two researchers. 30 studies were included in this systematic review. All articles selected were assessed as to their methodological quality. The results showed a predominance of qualitative studies for stress assessment among sports coaches. Moreover, it was observed that the coaches were affected by both organisational stressors, such as social isolation, poor training facilities, the need to manage conflict and interference of the athletes’ relatives during training sessions and competitions, and performance stressors, namely, concern with their performance and the athletes’ performance, pressure from the media and the managers to achieve results and concern with the athletes’ injuries. Thus, the results show that the stressors affecting sports coaches are multifactorial and are related to the level of competition of these professionals.